Bio-based refinery intermediate production via hydrodeoxygenation of fast pyrolysis bio-oil. (May 2021) - Dimitriadis, Athanasios; Chrysikou, Loukia P.; Meletidis, George; Terzis, George; Auersvald, Miloš; Kubička, David; Bezergianni, Stella
Abstract: Pyrolysis bio-oil is unsuitable as transportation fuel due to its chemical composition and high oxygen (>30 wt%) and water (>20 wt%) content rendering the upgrading essential prior any downstream use. The current work investigates the upgrading of a flash pyrolysis bio-oil via mild hydrotreatment (HDT), targeting to a potential intermediate refinery feed. Various operating parameters of HDT were tested, including three temperatures (573, 603 and 633 K), two pressures (4 and 7 MPa) and two H2 /bio-oil ratios (506 and 843 NL/L). According to the results, during HDT of bio-oil, massive plugging by coke formed in the reactor. The unsaturated oxygenates in bio-oil are regarded as the predominant coke precursors since they can interact with the catalytic surface. From all the examined conditions, it was found that the longest catalyst life, (5 days on stream), was achieved at 7 MPa pressure, 843 NL/L H2 /bio-oil ratio and 603 K temperature. Furthermore, several properties of the initial bio-oil were improved, such as viscosity (156 → 4.9 cSt), carboxylic acids (78 → 0.2 mgKOH/g), density (1.024 → 0.9162 g/ml), and oxygen content (37 → 4 wt%). Conclusively, mild HDT constitutes a promising technological pathway for bio-oil upgrading towards a reliable intermediate refinery feed. Graphical abstract: Image 1 Highlights: Bio-oil mild hydrotreatment leads to an upgraded intermediate refinery stream. HDT bio-oil can be used for hybrid fuel production. The dissolved water of bio-oil was totally removed as aqueous phase. Higher reaction temperatures favor HDO and cracking reactions. Higher reaction pressures and H2 /bio-oil ratios favor the catalyst life expectancy.